ADIPOSE-DERIVED STEM CELL TRANSPLANTATION ON URETHRAL MICROVESSEL AND VOIDING FUNCTION - Mahadi, Endi Prilansa; Hardjowijoto, Sunaryo; Alif, Sabilal; Purwati, Purwati; Sandhika, Willy; Budiono, Budiono (Indonesian Urological Association, 2015)
Objective: To examine the effects of adipose-derived stem cell (ADSC) transplantation on urethral tissue microvessel and voiding function on artificial stress urinary incontinence (SUI) in rats. Material & methods: 25 of 32 female wistar rats underwent vaginal distension as animal-SUI model. ADSCs were isolated from the peri-ovary fat, examined for stem cell properties, and labeled with PKH-2. Seven rats without vaginal distension and periurethral ADSCs injection as control. Twelve rats received periurethral injection of phosphate buffer saline as plasebo and 13 rats received periurethral injection of ADSCs. 14 and 28 days later, voided volume was meassured with voided stained on paper and microvessel density was meassured with immunohistochemical analysis (factor VIII R-Ag). Results: Voided volume analysis showed that rats in the plasebo group had abnormal voided volume compare to normal rats in day 14 (168.5 ± 119.05l vs 621.21 ± 283.85l; p < 0.05), and insignificant improvement of voided volume compare to normal rats in day 28 (852.09 ± 626.7l vs 868.49 ± 578.0l; p > 0.05). While in the ADSCs group only showed significant improvement of voided volume compare to abnormal rats in days 14 (379.35 ± 191.74l vs 228.18 ± 56.26l; p < 0.05). Immunohistochemical analysis showed that microvessel density higher in the ADSCs group compare to plasebo group in days 28 (12.86 ± 2.5 vs 9.50 ± 1.64; p < 0.05). Conclusion: ADSCs transplantation promotes improvements voided volume and urethral microvessel in the rat-SUI model. Keywords: Adipose-derived stem cell, vaginal distension, voided stained on paper, microvessel density.